The impact of the social relief & distress grant on poverty in South Africa - Fatch, Martha (School of Economics, 2025)
This paper examines the impact of the Social Relief & Distress grant on poverty reduction in South Africa amidst the COVID-19 global pandemic. A large number of individuals live below the poverty line in South Africa and the lockdowns used to combat the spread of COVID-19 have resulted in more people living below the poverty line. This paper uses secondary data in South Africa, utilising all five waves of the NIDS-CRAM panel survey, with an initial sample frame of 7,073 participants. This data is used to estimate the impact of a new cash transfer on household poverty using a number of different techniques. In initial estimates, a strong negative correlation between receipt of the Social Relief & Distress grant and household poverty is observed, as expected. However, in multivariate analysis this negative association is reduced, with an effect found which is neither practically nor statistically significant. While the SRD could reduce some proportion of household poverty in certain samples, this effect is not large enough to meaningfully impact average household socio-economic status in South Africa. Increasing the grant size and broadening its reach could have a significant impact on household poverty and overall inequality.